Exploiting photosynthesis-driven P450 activity to produce indican in tobacco chloroplasts - Mellor, Silas B.; Behrendorff, James B. Y. H.; Ipsen, Johan Ø.; Crocoll, Christoph; Laursen, Tomas; Gillam, Elizabeth M. J.; Pribil, Mathias (Frontiers in Plant Science, 2023)
Photosynthetic organelles offer attractive features for engineering small molecule bioproduction by their ability to convert solar energy into chemical energy required for metabolism. The possibility to couple biochemical production directly to photosynthetic assimilation as a source of energy and substrates has intrigued metabolic engineers. Specifically, the chemical diversity found in plants often relies on cytochrome P450-mediated hydroxylations that depend on reductant supply for catalysis and which often lead to metabolic bottlenecks for heterologous production of complex molecules. By directing P450 enzymes to plant chloroplasts one can elegantly deal with such redox prerequisites. In this study, we explore the capacity of the plant photosynthetic machinery to drive P450-dependent formation of the indigo precursor indoxyl-β-D-glucoside (indican) by targeting an engineered indican biosynthetic pathway to tobacco (Nicotiana benthamiana) chloroplasts. We show that both native and engineered variants belonging to the human CYP2 family are catalytically active in chloroplasts when driven by photosynthetic reducing power and optimize construct designs to improve productivity. However, while increasing supply of tryptophan leads to an increase in indole accumulation, it does not improve indican productivity, suggesting that P450 activity limits overall productivity. Co-expression of different redox partners also does not improve productivity, indicating that supply of reducing power is not a bottleneck. Finally, in vitro kinetic measurements showed that the different redox partners were efficiently reduced by photosystem I but plant ferredoxin provided the highest light-dependent P450 activity. This study demonstrates the inherent ability of photosynthesis to support P450-dependent metabolic pathways. Plants and photosynthetic microbes are therefore uniquely suited for engineering P450-dependent metabolic pathways regardless of enzyme origin. Our findings have implications for metabolic engineering in photosynthetic hosts for production of high-value chemicals or drug metabolites for pharmacological studies.